APAKAH MEMERLUKAN MEDIASI? PERAN ORGANISASI PEMBELAJAR DAN DUKUNGANNYA UNTUK MENGURANGI NIAT KELUAR KARYAWAN - Nury Ariani Wulansari; Danik Setyaningrum (Jurnal Manajemen dan Pemasaran Jasa, 2016)
The purpose of this study was to examine the influence of organizational learning culture and perceived organizational support on turnover intention with organizational citizenship behaviour as intervening variable. The sample of this study was employees of 3 Star Hotel in Semarang as many 166 respondents using propotional random sampling.The method used in collecting the data was a questionnaire which was measured by likert scale. The methods of data analysis were descriptive analysis, regression analysis, and bootstrapping analysis. The results of thie study showed that organizational learning culture and perceived organizational support have positive effect on OCB and negative effect on turnover intention. This study also supported the previous research that OCB mediated organizational learning culture and perceived organizational support on turnover intention in employees of 3 Star Hotel in Semarang. For further research, it is expected to test the different mediating variables in this research model, such as self-efficacy, self-esteem and locus of control.